Determinants of Things Affecting Tax Avoidance Behavior Case Study of Manufacturing Companies For 2016-2020 - Asyari; Awaloedin, Dipa Teruna; Achyarsyah, Padri; Dewi, Dyah Handayani (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Companies use various ways to reduce their tax burden, this is a business choice that is made when there is a decrease in income, an increase in operational costs, and unstable economic conditions. This research aims to empirically test things that influence tax avoidance behaviour with the variables profitability, leverage, sales growth, and fixed intensity using a study of manufacturing sector companies in 2016-2020. Analysis of financial report data with a sample of 26 companies. The sampling method was purposive sampling with the help of SPSS 25 multiple linear regression analysis software. The research results show that profitability has a significant positive effect on tax avoidance. leverage and sales growth do not affect tax avoidance, while fixed asset intensity has a negative effect on tax avoidance.